Comparison of the effects of 6 weeks of squat training with a plyometric training programme upon different physical performance tests in adolescent team handball players - van den Tillaar, R.; Waade, L.; Roaas, T. (Acta Kinesiologiae Universitatis Tartuensis, 2015)
The purpose of this study was to compare the effects of six weeks of squat training with those of plyometric training upon different types of physical performance in adolescent male and female team handball players. Twenty-six adolescent male and female team handball players (age 13.8±0.5 yr, body mass 57.5±11.5 kg, body height 1.70±0.10 m) participated in the study. Half of the subjects (n=13) conducted a squat training program, while the other half conducted a plyometric training program, twice a week for six weeks, in addition to their normal team handball practice. Both groups increased their performance after six weeks in agility, 30 m sprint and Yo-Yo IR1 tests, while no changes were found in the CMJ, strength test and throwing velocity. The results suggest that either a short in-season 6-week squat orplyometric training regimen can improve the physical performance of the lower body, while these programs will not enhance the performance of the upper body.